Report on Infrastructure for Export of Agricultural Commodities And Processed Food - Planning Commission (Planning Commission, 1991)
Our analysis shows that while considerable development has taken place in agriculture, the appropriate linkages for marketing, quality control, storage and other facilities are lacking for building a proper base for exports. While Indian agriculture production-wise, is ready for a take-off, there are certain necessary infrastructure which need to be built up fast enough to establish a competitive presence in the global market. The first and foremost is the need to have a comprehensive agro-export policy and a suitable strategy to establish the necessary in-house facilities for the farmers in the areas of plenty in terms of production, quality and exportable surplus. There is need to improve the investment climate to encourage growers and their associations so that entrepreneurs have access to knowledge of modern technologies for cultivation and processing, consistency in supply and competitive cost of production.
Government of India Planning Commission (Agriculture Division)
Government of India Planning Commission (Agriculture Division)